A Bibliometrics Analysis of Multimedia Forensics and Deep Learning Research Based on Scopus Index - Erika Ramadhani; Dedy Hariyadi (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2023)
Forensics of digital data are concerned with identifying, acquiring, processing, analysing, and reporting on electronic data. Multimedia forensics focuses on investigating computer crimes using forensic methods. The analysis of multimedia evidence is the role of multimedia forensics, on the other hand. In the analysis, digital evidence is evaluated scientifically to maintain its integrity, to find its source, and to authenticate it. There are several methods in multimedia forensics, such as the implementation of deep learning. The purpose of this research is to conduct bibliometric analysis in multimedia forensics and deep learning by using the data gathered from Scopus index on the keyword “multimedia forensics and deep learning”. The result is 68 relevant papers were found in the range of 2017-2022. The results of this research can be used by researchers as a reference when conducting research and determining the research themes to be pursued.